Soviet factography reality without realism - Fore, Devin 1972- (The University of Chicago Press, 2024)
"All the Graphs is the first full study of factography, an aesthetic movement in Soviet modernism that flourished briefly in the 1920s before Stalinism took hold. Devin Fore charts the movement through the work of its key figures, most prominently writer Sergei Tret'iakov, and its position in the material culture of the early Soviet period. Factography was a set of photography and film practices preoccupied with the inscription of facts. The movement was related to several contemporary efforts throughout the world to forge a basis for the production of documentary projects. Committed to a present uncoupled from both the past and the future, the factographers were engaged in chronicling modernization and how it was transforming human experience and society. Fore explains how it is impossible to comprehend the factographic project without considering the explosion of new media technologies and their mass-cultural formations: radio broadcasting, sound in film, photo-media innovations that allowed the illustrated press to flourish. New media became ordinary facts of life, and the factographers made it their mission to document the great industrial campaigns of the day-the promulgation of "progress." All the Graphs elucidates how the factographers created heterogenous, experimental techniques of documentation responsive to the new social and cultural realities of Soviet Russia and, as Fore demonstrates, distinct from our current, codified concept of documentary. This fascinating intellectual history of early Soviet materialist thought is required reading for anyone interested in Soviet culture, the interwar avant-gardes, aesthetics, and the theory of documentary"--
Keywords: Geschichte 1928-1931; Dokumentarfilm; Faction-Prosa; Sowjetunion; Documentary mass media / Soviet Union; Documentary photography / Soviet Union; Reportage literature, Russian / Soviet Union; Modernism (Aesthetics) / Soviet Union; Médias documentaires / URSS.; Photographie documentaire / URSS.; Modernisme (Esthétique) / URSS.